2017
DOI: 10.1152/ajpendo.00049.2017
|View full text |Cite
|
Sign up to set email alerts
|

Brown adipose tissue activation in a rat model of Parkinson’s disease

Abstract: Loss of body weight and fat mass is one of the nonmotor symptoms of Parkinson's disease (PD). Weight loss is due primarily to reduced energy intake and increased energy expenditure. Whereas inadequate energy intake in PD patients is caused mainly by appetite loss and impaired gastrointestinal absorption, the underlying mechanisms for increased energy expenditure remain largely unknown. Brown adipose tissue (BAT), a key thermogenic tissue in humans and other mammals, plays an important role in thermoregulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…Currently, an ablation of nerve bundles of bilateral BAT was used to abolish the function of BAT in vivo. In consistence with previous studies (48,49,61), the surgical denervation was confirmed by the significant elimination of TH in BAT in the current study. We found that whitening occurred in denervated of BAT as evidenced by the uniocular morphology and decreased levels of UCP1 protein.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Currently, an ablation of nerve bundles of bilateral BAT was used to abolish the function of BAT in vivo. In consistence with previous studies (48,49,61), the surgical denervation was confirmed by the significant elimination of TH in BAT in the current study. We found that whitening occurred in denervated of BAT as evidenced by the uniocular morphology and decreased levels of UCP1 protein.…”
Section: Discussionsupporting
confidence: 93%
“…As previous descriptions (49)(50)(51)(52), mice received a surgical denervation or removal of BAT. Under a stereomicroscope, a midline incision in the skin was performed along the upper dorsal surface.…”
Section: Surgical Denervation and Removal Of Batmentioning
confidence: 99%
“…Thermogenesis was identified as a deimination enriched KEGG pathway. Loss of body weight and fat mass is one of the non-motor symptoms of Parkinson's disease and has, amongst others, been related to brown fat tissue meditated thermogenesis [56]. Thermogenesis is related to mitochondrial function [57,58] and also linked to synaptic transmission and neurodegeneration [59].…”
Section: Discussionmentioning
confidence: 99%
“…RNA concentration was about 1500-3000 ng/μl determined with NanoDrop2000. Quantitative real-time reverse transcription polymerase chain reaction (qRT-PCR) analysis was performed as previously described [32]. The primer sets we used were as Table S.1.…”
Section: Coimmunoprecipitation and Gst Pull-down Assaysmentioning
confidence: 99%